Calculation Array Solar Panel Capacity of 50 kWP Pamulang University South Tangerang - Triyanto, Aripin; Rozak, Ojak Abdul; Aditya, Aditya (Program Studi Teknik Elektro Universitas Khairun, 2023)
Pamulang University is located in the South Tangerang area consisting of three buildings and 6 faculties and 5 of them are engineering faculties. Currently implementing Solar Panels is being carried out by the Faculty of Electrical Engineering, namely the application of new renewable energy sources. Installation of a solar power plant with a capacity of 50 KWP On-Grid is used as a provider of electricity for building lighting. The purpose of calculating the number of arrays is to determine the area and output power of the arranged solar panels. The problems faced before installation are the number of solar panels that will be arranged in the rooftop area, the amount of solar radiation and the output power. The use of research methods through the stages of calculation, monitoring, and standardization references was carried out for two weeks. The measuring instrument used in the research is the Seaward Solar Survey 200R, while the Global Solar Atlas (GSA) is used as a reference for insolation values in December 2022. The calculation results for the area of the array are 325.62 mÂ², the PLTS electrical energy (EL) calculation is 393, 12 kWh, GSA of 6.14 kWh /mÂ²/day, temperature correction factor (TCF) of 0.96, number of PLTS 102 solar panels with 6 PV strings, highest inverter output of 272.8 kWh and lowest value of 133.2 kWh